Synthesis and Thermophysical Properties of Trioctyl Phosphonium - Based Mono and Dicationic Room Temperature Ionic Liquids Incorporating Dioctylsulfosuccinate Anion. - K. Ziyada, Abobakr; D. Wilfred, Cecilia (Gezira Journal of Engineering and Applied Sciences, 2018)
A new series of monocationic (MILs) and symmetrical dicationic (DILs) trioctyphosphonium-based room temperature ionic liquids (RTILs) incorporating dioctylsulfosuccinate(DOSS)anionnamely,trioctyltetradecylphosphoniumdioctylsulfosuccinate;[P 8,8,8,14 ]DOSS,1,10-bis (trioctylphosphonium) decane diocty lsulfosuccinate; [P 8,8,8 C 10 P 8,8,8 ]DOSS,1,6-bis(trioctylphosphonium)hexane dioctylsulfosuccinate; [P 8,8,8 C 6 P 8,8,8 ]DOSS have been prepared. The present ionic liquids (ILs) are characterised using NMR and elemental analysis and their physical properties such as density, viscosity and refractive index have been performed at a broad range of temperature (293.15 to 353.15) K and at atmospheric pressure. The present MILs possesses lower densities and higher viscosities comparable to the MILs with short alkyl chain while DILs possesses higher viscosities comparable to the MILs. The higher viscosity of the present ILs is due to the increased Van der Waals interactions resulting from the long alkyl chains of the cation and anion along with the large volume of the docusate anion which results in low ion mobility due to the electrostatic interaction between the cation and anion. The coefficient of thermal expansion, crystal energy and molar refraction were calculated from the experimental values of density and refractive index. These ILs show a weak temperature dependency on the  thermal expansion coefficient and low crystal energy.